The Regional Nexus of Economic Growth, Income Inequality and Poverty - Naufal, Abyan; Fikriah, Fikriah (Ekonomikalia Journal of Economics, 2023)
This study divides Aceh Province into three distinct regional to investigate the nexus between economic growth, income inequality, and poverty from 2011-2021. Applying the Granger causality test across 23 districts/cities, this research uncovers the distinct interplay among these pivotal socioeconomic variables. While previous studies have delved into these relationships in various contexts, the unique socio-economic backdrop of Aceh Province commands a targeted empirical exploration. Across the province, our findings indicate a bidirectional causality between economic growth and poverty, elucidating a reciprocal influence where economic dynamics and poverty levels directly affect each other. Additionally, we observe a unidirectional causality from income inequality to economic growth and poverty, demonstrating that income inequality hampers regional economic growth and exacerbates poverty levels. In regional 1, a self-sustaining causal loop is identified, where economic growth leads to changes in poverty, which then feed into income inequality, and subsequently loop back to impact economic growth. In regional 2, a bidirectional causality between economic growth and poverty is found, highlighting a relationship where economic progress alone does not effectively address poverty. Regional 3 presents a distinctive pattern, where income inequality is a precursor to poverty, which then unidirectionally impacts economic growth, suggesting that in this region, strategies to combat inequality could be pivotal in spurring economic development. These varied regional causal patterns signal the need for nuanced and region-specific policy interventions.